Identifikasi Faktor-Faktor Penumpukan Realisasi Anggaran Belanja Di Akhir Tahun (Studi Kasus Pada Balai Penelitian Dan Pengembangan Lingkungan Hidup Dan Kehutanan Manado) - Sudarwati, Nina; Karamoy, Herman; Pontoh, Winston (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2017)
Abstract. Implementation of the budget is a very important stage in the realization of government programs that have been organized in the National budget. The implementation sometime found difficulties, including the realization of the budget tends to be low in the early years and accumulated at the end of the year. According to Rusqiayati (2014), ideally the realization of the government's budget follows the "S-curve" which is tends to be stable at the beginning of the year, then increased in the mid and stabilized towards the end of the fiscal year. This research aims to identify factors that causing the accumutaed of budget realization in the end of the year at Environment and Forestry Research and Development Institute of Manado. This study is a qualitative case study. The key informants in this research areÂ  officers or employees directly involved in financial management, such as the Budget Authority (KPA), Committing Officer (CO), official signing of Warrant Pay (PPSPM), Treasurer, Assistant Treasurer, and Executive Technical Officer ( PTK).The results showed thatÂ  factors that causing the accumulated of budget realization in the end of the year at Environment and Forestry Research and Development Institute of ManadoÂ  were budget planning, budget execution, procurement of goods/services, and human resources. Keywords: Accumulation, Budget realization, Thematic Analysis Abstrak Pelaksanaan anggaran merupakan tahap yang sangat peting dalam merealisasikan program dan kegiatan pemerintah yang telah disusun dalam APBN. Dalam pelaksanaan mengalami berbagai kendala, diantaranya realisasi anggaran yang cenderung rendah di awal tahun dan menumpuk di akhir tahun. Menurut Rusqiayati (2014) idealnya, realisasi anggaran pemerintah mengikuti â€œKurva Sâ€ yaitu cenderung stabil di awal tahun, kemudian meningkat pada pertengahan, dan kembali stabil menjelang akhir tahun anggaran. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor yang menyebabkan penumpukan realisasi anggaran di akhir tahun pada Balai Penelitian dan Pengembangan Lingkungan Hidup dan Kehutanan Manado. Penelitian ini menggunakan metode kualitatif studi kasus. Informan kunci penelitian ini adalah pejabat atau pegawai yang terlibat langsung dalam pengelolaan keuangan, seperti Kuasa Pengguna Anggaran (KPA), Pejabat Pembuat Komitmen (PPK), Pejabat Penandatangan Surat Perintah Bayar (PPSPM), Bendahara Pengeluaran, Pembantu Bendahara, dan Pelaksana Teknis Kegiatan (PTK). Hasil penelitian menunjukkan bahwa faktor-faktor yang menyebabkan penumpukan realisasi anggaran belanja di akhir tahun pada Balai Penelitian dan Pengembangan Lingkungan Hidup dan Kehutanan Manado yaitu perencanaan anggaran, pelaksanaan anggaran, pengadaan barang/jasa, dan sumber daya manusia. Kata Kunci : Penumpukan, Realisasi Anggaran Belanja, Analisis Tematik